Process Parametrs Affecting the Hydrogen Production by Water Electrolysis and Electrolyser Characteristic - Nabil, Bouazizi; Romdhane, Ben Slama; Radhouane, Bargougui; Bechir, Chaouachi (International Journal of Chemical and Process Engineering Research, 2015)
The hydrogen production by solar electrolysis depends on the distance between the electrode and the test tube. In fact, the height (h = 3cm) was the best taken as a parameter while relying on the rate of production as a measure of effectiveness. Raising the temperature increases the input electrolyzer voltage, which results in a temperature rise electrolyte to a value of 8.2V at 100 °C. Sunshine is strongly influenced the hydrogen production where changes from one site to another. The effects of the salinity degrees is investigated, which displayed a decrease of the hydrogen flow for the salt masses included between 50 and 130 g/l. Additionally, the current density was higher in acid-base environment, and lower in neutral for pH values around 6.4 and 8.4. Moreover, the hydrogen flow was higher for the electrolyte based margin.